THE IMPACT OF THE QUALITY OF EXTERNAL CONTROL ON RAISING THE EFFICIENCY OF THE TAX EXAMINATION PROCESS - Nadhim Khasran Hassooni Al Shaibani; Sadiq Jafar Kathim; Hayder Salim Mousa Al-Zubaidi (Scholars Digest Publishing, 2024)
The purpose of this research is to disclose the effect of the quality of external control in raising the efficiency of the tax examination process at a sample of the guesses, auditors, officials of units, departments, and the people in the General Authority for Taxes in Iraq, as the research sample (30) workers from the aforementioned sample was represented by using the descriptive analytical approach , And in order to reach the best results, the statistical package (spss.v.29) was used, and on the basis of that the research reached the existence of an effect of the quality of external control in raising the efficiency of the tax examination process, which means that the quality of external control depends on independence, objectivity and the percentage of fees that He receives it, the procedures and the policies he followed when performing his work, as the study came out with several recommendations, the forefront of which was the necessity of cooperation between the efforts made in the Professional Council and the Accountants Syndicate and auditors to keep pace with the developments taking place in the field of accounting and constantly in a way that achieves quality in external control, as well as working to develop policies and procedures It helps in increasing the process of supervision and follow -up to apply the standards of quality control and external audit.
Keywords: External control, Tax examination.